The road to eco-efficiency: can ecological civilization pilot zone be useful? New evidence from China - Chai, Zeyang; Guo, Feng; Cao, Jianhong; Yang, Xiaodong (Routledge, 2024)
Ecological civilization construction is an important dimension to achieve high-quality economic development. This paper evaluates the eco-efficiency improvement effect of China’s ecological civilization pilot zone policy utilizing the synthetic control method (SCM) differences-in-differences method (DID) and examines the influence mechanism of ecological civilization pilot zones on eco-efficiency in the light of the environmental pollution penalty, green technological innovation, and environmental publicity and education. The study results indicate that the construction of the ecological civilization pilot zone policy has substantially boosted eco-efficiency in the pilot areas, with the strongest boosting effect on eco-efficiency in Fujian province, followed by Guizhou province, and not significantly on eco-efficiency in Jiangxi province. Further, this paper also reveals that the construction of ecological civilization pilot zones has effectively contributed to eco-efficiency through channels such as strengthening the environmental pollution penalty, stimulating green technological innovation, and broadening environmental publicity and education.